Electrochemical Applications of Metal-Organic Frameworks: Overview, Challenges, and Perspectives - Salazar-Gonzalez, R; Candia-Onfray, C; Candia-Onfray, C (American Chemical Society, 2021)
Applications for Biomass Conversion and CO2Capture. Metal-organic frameworks (MOFs) have emerged as highly customizable catalysts based on their unique features. Recent studies have developed specific MOFs for many applications. As part of a three-volume set (1393-1395), this volume provides an overview on MOFs used in electrochemical applications, including synthesis, characterization, and examples of applications. Materials scientists and chemical engineers will find this work useful, as will students learning about this active area of research. © 2021 American Chemical Society. All rights reserved.